Retrospective analysis of the main indicators of Kosiv CRH efficiency for the period 2014–2018 - Stovban, Mykola; Tolstanov, Alexandr; Kravchenko, Oleksiy (ScienceRise: Medical Science, 2022)
This article presents a retrospective analysis relating to the main performance indicators of the Kosovo Central District Hospital (CDH). The author's method of calculating the efficiency of the hospital on the components of medical, social and economic efficiency is proposed. The reason for the low level of efficiency of the Kosovo CDH is substantiated and ways to increase the efficiency are suggested. The aim of this article is to conduct a retrospective analysis of the effectiveness of the Kosiv Central District Hospital to identify the main problems of local hospitals and to formulate scientifically sound proposals for improving the medical system in the newly formed united territorial communities. Research methods. In the article were used general scientific research methods: Analysis and synthesis, in the study of scientific literature and determining the effectiveness of the Kosiv CDH; Economic and statistical analysis and comparison, when calculating indicators of medical, social and economic efficiency of the Kosiv CDH, Generalization - when developing recommendations for improving the efficiency of the Kosiv CDH. Results: The author's method of calculating indicators for assessing the medical, social, and economic efficiency of the Kosiv CDH was developed. A retrospective analysis of the effectiveness of the Kosiv CDH was conducted, which allowed us to state the low level of efficiency, which was formed under the influence of factors independent of the hospital itself. The necessity of introduction of paid medical services and their realization by the Kosiv CDH, development of public-private partnership and the mechanism of acquisition of the diagnostic car for realization of programs on complex diagnostics of health of the population of the Kosiv city united territorial community are substantiated. Conclusions. A retrospective analysis of the effectiveness of the Kosiv CDH in 2014-2018 allowed us to conclude that the level of such efficiency is quite low. However, the low level of efficiency of the Kosiv CDH is due to the existing principles of medical development in Ukraine, which is, “de jure” based on the concept of free medical care